The changes in amino acids composition of the blood associated with reproductive losses and their correction - Алієва, Тарана Джафар кизи (ScienceRise: Medical Science, 2016)
The results of examination of women with reproductive losses (RL) in anamnesis, realized within medical-genetic consultation for explanation of the role of changes of heterochromatin (chromosome polymorphism) and the features of folate metabolism in women with RL with the perspective of individualization of preconception support on the base of determination of character of causal relation between these phenomena, were presented in the article. Aim of research: specification of the role of chromosome polymorphism and changes of amino acid composition of blood in women as the possible markers of high risk of RL. Material and methods: two groups of women were examined: I - 154 observations with obstetric anamnesis, complicated with RL and II - 32 practically healthy women with non-complicated reproductive anamnesis, who underwent preconception prophylaxis before planning of pregnancy. The genealogical anamnesis, features of the state of internal organs, genitals were studied. The special studies included cytogenetic analysis, determination of the level of free sulfur-containing amino acids (methionine, cystine, cysteine, taurine) by the method of highly effective liquid chromatography. Results: The frequency of structural changes of chromosomes in women with RL is 36,4 %. The types of slight chromosome anomalies in 3,9 % was the carriage of extremal variants of C-polymorphism; in 18,8 % – polymorphism of adjacent districts of chromosomes 13, 14, 15, 17, 21, 22; in 1,9 % – increased size of сentromere heterochromatin in chromosome; in isolated cases – the increase of linear sizes of heterochromatin districts of 9 chromosome and combination of polymorphism of adjacent districts of 15 chromosomes. In 7,1 % of cases polymorphism of adjacent districts of 21 chromosome was detected. The statistical connection between the carriage of chromosome and gene polymorphism in women with RL in anamnesis was detected. The significant difference between the main and control groups was detected only for methionine among sulfur-containing amino acids. Hyperhomocysteinemia was detected in 71,9 % of women of the main group. Conclusions: Preventive strategy as to reproductive losses must provide the timely diagnostics and correction of disorders of folate cycle that is determinative component of personalized primary prophylaxis of the disorder of reproductive function of family in the modern Ukrainian population